Cultural effects on cancer prevention behaviors : fatalistic cancer beliefs and risk optimism among Asians in Singapore - Kim, Hye Kyung (2020)
Although culture is acknowledged as an important factor that influences health, little is known about cultural differences pertaining to cancer-related beliefs and prevention behaviors. This study examines two culturally influenced beliefs-fatalistic beliefs about cancer prevention, and optimistic beliefs about cancer risk-to identify reasons for cultural disparity in the engagement of cancer prevention behaviors. We utilized data from national surveys of European Americans in the United States (Health Information National Trends Survey 4, Cycle3; N = 1,139) and Asians in Singapore (N = 1,200) to make cultural comparisons. The odds of an Asian adhering to prevention recommendations were less than half the odds of a European American, with the exception of smoking avoidance. Compared to European Americans, Asians were more optimistic about their cancer risk both in an absolute and a comparative sense, and held stronger fatalistic beliefs about cancer prevention. Mediation analyses revealed that fatalistic beliefs and absolute risk optimism among Asians partially explain their lower engagement in prevention behaviors, whereas comparative risk optimism increases their likelihood of adhering to prevention behaviors. Our findings underscore the need for developing culturally targeted interventions in communicating cancer causes and prevention.